A dye – sensitized solar cell module with enhanced charge collection efficiency - Azhar, Fakharuddin (2015)
Intense research in the field of dye-sensitized solar cells (DSCs) brought them to a level of delivering ~13% efficiency (η) using mesoporous TiO2 particles, inorganic dyes, and redox electrolyte. High η and IPCEs are so far reported in devices of rather smaller area (≤ 0.2 cm2), a size that put limitations on the scalability of the device. On the other hand, large area modules (DSMs) are developed by up scaling the DSCs to give either added voltages (series connection), such as S –type, W–type and Z–type, or currents (parallel connection) with appreciable output voltage (~8 V) and current (~2 – 3 A), respectively, in separate devices of active areas in the 20 – 1000 cm2 range. The highest achieved in DSMs is ~ 8.2%, ~36% smaller than their laboratory scale devices. We note that such designs are invariably built in the form of interconnected TiO2 strips (≥ 3 cm2) and the photocurrent density (JSC) in these designs is merely 30 – 50 % then that of single cells. We have investigated the effects of DSC photoelectrode area upon its  and identified that, within the limits of our study, threshold area is the key in achieving the JSC and clearly not the expanded photoelectrode area as adopted conventionally in a DSM fabrication. Upon increasing the photoelectrode area, the  decreased biexponentially, the main contributor to which was the JSC. The upshots of the electrochemical studies revealed that the electrons from an area above a threshold are never collected due to a competition between electron lifetime (τn) and transit time (τd). We suggest that if larger electrodes are fabricated, then electrons from smaller spatial domains contribute to the short circuit current density. The diffusion length (Ln) in DSCs, which is defined as the distance travelled by electrons before recombining with the hole species in electrolyte, L= (Dnn)1/2, where Dn is the electron diffusivity, considered only film thickness so far. Our findings reveal that area of the electrode is also to be considered when the L is defined. Based on the insights, we fabricated alternative designs to build DSMs with increased charge collection (c). In our specially designed experiments, we altered the photoelectrode design by splitting the electrode into multiple fractions to restrict the electron diffusion pathways. We observed a correlation between the device physical dimensions and its charge collection efficiency via current-voltage and impedance spectroscopy measurements. Our electrode designs showed >50 % increased JSC due to shorter τd, higher recombination resistance and 20 – 50% higher c compared to the conventional ones despite their similar active volume (~3.36 × 10-4 cm3). If high efficiency DSCs is targeted using commercial TiO2 paste on account of its high specific surface area, results from our studies would be helpful in designing new device structures to build high efficiency DSMs